Concurrent somatic KRAS mutation and germline 10q22.3-q23.2 deletion in a patient with juvenile myelomonocytic leukemia, developmental delay, and multiple malformations: a case report - Ruen Yao; Tingting Yu; Yufei Xu; Guoqiang Li; Lei Yin; Yunfang Zhou; Jian Wang; Zhilong Yan (BMC, 2018)
Abstract Background The proto-oncogene KRAS performs an essential function in normal tissue signaling, and the mutation of KRAS gene is a key step in the development of many cancers. Somatic KRAS mutations are often detected in patients with solid and non-solid tumors, whereas germline KRAS mutations are implicated in patients with the Noonan syndrome, cardio-facio-cutaneous (CFC) syndrome and Costello syndrome. The deletion of chromosome 10q22.3-q23.2 is a rare cytogenetic abnormality, which often leads to distinct facial appearance and delays in speech and global development. Case presentation Herein, we report the case of a 4-year-old boy diagnosed with juvenile myelomonocytic leukemia. The boy also had syndromic features, such as speech and motor developmental delay, multiple congenital malformations, including distinct facial features, club feet, and cryptorchidism. Using whole-exome sequencing, we identified a pathogenic mutation in KRAS [c.34G > A, p.Gly12Ser] isolated from peripheral blood DNA. Sanger sequencing confirmed the wild-type sequence in the parents and patient's salivary cell DNA indicating its somatic state. A 7311-kb deletion in 10q22.3-q23.2 was also revealed by chromosomal microarray analysis, which was later proved as a germline de novo variant. Conclusion Juvenile myelomonocytic leukemia in the patient was attributed to a somatic KRAS mutation, whereas the syndromic features of the patient were considered a consequence of germline chromosome 10q22.3-q23.2 deletion. Genetic testing for patients with complicated phenotypes can be valuable in detecting multiple pathogenic variants.